2017
DOI: 10.24247/ijmperdjun201726
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study of Aerospace Material during Fabrication of V Groove using WEDM

Abstract: In this experimental study, the machining parameters, tool electrode, current, pulse on time, pulse of time, wire feed and wire tension has been studied using Inconel-625 as work piece in Wire electrical discharge machining (WEDM).The optimization of these parameters is very crucial for the greatest manufacturing results and production at the lowest cost. In order to get the maximum output from these industries, the material removal rate and surface roughness should be optimized. The experiment has been execut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The stimulus of changed process parameters on the white layer thickness was studied, providing insights into optimizing the machining parameters for enhanced EDM performance [6]. Few studies were focused on Inconel 718, a widely used Ni-based superalloy; this research investigates the white layer formation during wire EDM [7]. The authors discovered the characteristics of Ti-6Al-4V with rotary ultrasonic-assisted EDM [8].…”
Section: Introductory Theorymentioning
confidence: 99%
“…The stimulus of changed process parameters on the white layer thickness was studied, providing insights into optimizing the machining parameters for enhanced EDM performance [6]. Few studies were focused on Inconel 718, a widely used Ni-based superalloy; this research investigates the white layer formation during wire EDM [7]. The authors discovered the characteristics of Ti-6Al-4V with rotary ultrasonic-assisted EDM [8].…”
Section: Introductory Theorymentioning
confidence: 99%
“…It was concluded that the PW and PI are the most important factors that enhance the WEDM performance [15]. The CR and surface finish of cryogenically cooled aerospace component material had been improved in EDM experiments [16]. The effects of various cutting parameters on surface cracks and white-layer formation have been analyzed using metal powder mixed dielectric fluid in the WEDM.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the effect of cryogenic treated and untreated tool on EDM tests have been performed out on Inconel-625 workpiece material. Influences of controlling factors on MRR and surface roughness have been investigated [39]. The electrode wear ratio and MRR were examined on a conventional EDM process using the TOPSIS approach [40].…”
Section: Introductionmentioning
confidence: 99%